STRATEGI PENATAAN RUANG BERBASIS MASYARAKAT DALAM PEMBANGUNAN BERKELANJUTAN DANAU TONDANO KABUPATEN MINAHASA - Sorongan, Elro Garry; Karwur, Denny; Kalangi, Johny A. F. (AGRI-SOSIOEKONOMI, 2022)
This research aims to analyze community-based spatial planning strategies in the sustainable development of Lake Tondano, Minahasa Regency. The method used in this study is a quantitative descriptive method which aims to describe the systematics, accuracy, accuracy, conditions and potentials including spatial problems in the management of sustainable development of Lake Tondano in Minahasa Regency. The sample used in this study amounted to 30 people with a sampling technique that is purposive sampling. Data collection was carried out by means of interviews, questionnaires and documentation which were analyzed using SWOT analysis, namely identifying external factors and internal factors regarding community-based spatial planning in the sustainable development of Lake Tondano in Minahasa Regency. The results of this study indicate that in the spatial planning process for the sustainable development of Lake Tondano in Minahasa Regency, there is no policy or local government regulation that specifically regulates it. The priority strategy in order to organize community-based space in the sustainable development of Lake Tondano, Minahasa Regency is to formulate a policy on spatial planning for saving and managing Lake Tondano.